Adherence to and effectiveness of guidelines for routine investigations of adult patients with mental and behavioural disturbances - Jere, Solomon (Division of General Surgery, 2024)
Background The process of medical clearance aims to exclude a general medical condition as an underlying cause for the mental and behavioural disorder and involves routine screening with special investigations. Mitchells Plain District Hospital's emergency centre follows the Western Cape Provincial guidelines when screening for general medical conditions in these patients. Adherance and effectiveness of these guidelines is unknown. Aim This study aimed to determine the effectiveness of and adherance to the Western Cape Provincial guidelines for routine investigations of adult patients with mental and behavioural disturbances presenting to a district level emergency centre. Methods This descriptive study was conducted at Mitchells Plain Hospital in Cape Town, South Africa. Data was collected from existing electronic registries over a 6-month period. Adult mental health care users were risk stratified into the probability of having a general medical condition according to provincial guidelines and the results of their special investigations were described against their outcome. Results Of the 688 patients included in this study, 66% had abnormal vital signs and of the 312 patients who received special investigations, 56% were abnormal, including 18% who were clinically significantly abnormal. Abnormal special investigations changed the clinical outcome for 3 (<1%) patients. Adherence to the provincial guidelines was reasonable (82%) but non-adherence resulted in numerous unnecessary investigations. Conclusion The results of this study support the existing evidence that clinical assessment and clinician gestalt should guide the need for special investigations and that there is no benefit to routine screening in the EC. The results also demonstrate reasonable adherence to the current guidelines even though this rarely changed patients' outcome. Decisions were based on clinical findings and clinician gestalt, and not abnormal special investigations or vital signs – which were both prevalent.